Rancang Bangun Distro “Langit Ketujuh” GNU/Linux sebagai Sistem Operasi Multimedia yang Solutif dan Merdeka - Rozi, Hervy Qurrotul Ainur; Fitrani, Arif Senja (Universitas Nusantara PGRI Kediri, 2022)
“LangitKetujuh” operating system is a GNU/Linux distribution derived from Void Linux. Carrying a multimedia concept, LangitKetujuh is specifically designed to meet graphic design needs. Such as illustration, 2D/3D animation, layout design, product design, game development, videography, audio production and other creative fields, but LangitKetujuh also supports general needs. This study aims to produce a complete and reliable desktop operating system in the multimedia world and maximize the performance of the user's machine. In addition, the LangitKetujuh is expected to be able to be used as an operating system in developing countries which can reduce the budget for HR training and proprietary software licenses by individuals, institutions, companies and governments.